Art and Liturgy Thoughts and Reflections on Beuronense Art in São Paulo - Rosângela Aparecida da Conceição (Anastasis: Research in Medieval Culture and Art)
We will present some thoughts and reflections on art and liturgy that will help us in understanding the new sacred artistic trends that emerged in the mid-19th century in Europe. The writings of Luigi Pareyson, Etienne Gilson and Albert Rouet were chosen for this exercise because their works contain questions about the relationship between art and aesthetics, sacred art and liturgy. We will continue with a brief study of the postulates of Peter Lenz about the Beuron aesthetics and their assimilation by other monasteries, as well as religious brotherhoods in São Paulo in the early 20th century.